1995
DOI: 10.1126/science.269.5221.187
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Trends and Lifetime of CH 3 CCI 3 and Global OH Concentrations

Abstract: Determination of the atmospheric concentrations and lifetime of trichloroethane (CH(3)CCI(3)) is very important in the context of global change. This halocarbon is involved in depletion of ozone, and the hydroxyl radical (OH) concentrations determined from its lifetime provide estimates of the lifetimes of most other hydrogen-containing gases involved in the ozone layer and climate. Global measurements of trichloroethane indicate rising concentrations before and declining concentrations after late 1991. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
365
2
5

Year Published

1997
1997
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 678 publications
(388 citation statements)
references
References 27 publications
16
365
2
5
Order By: Relevance
“…Methane has an atmospheric lifetime of 8.9±0.6 based on analyses of methyl chloroform and good knowledge of the loss rate with OH (Prinn et al, 1995). This is lower than the previous estimate of 10 years (WMO, 1991(WMO, , 1995.…”
Section: Ch 4 Sinkscontrasting
confidence: 47%
See 3 more Smart Citations
“…Methane has an atmospheric lifetime of 8.9±0.6 based on analyses of methyl chloroform and good knowledge of the loss rate with OH (Prinn et al, 1995). This is lower than the previous estimate of 10 years (WMO, 1991(WMO, , 1995.…”
Section: Ch 4 Sinkscontrasting
confidence: 47%
“…Observed trends in the seasonal cycle of methane, and global OH concentrations inferred from methylchloroform measurements do not support a significant change in OH over the past decades (Dlugokencky et al, 1997;Prinn et al, 1995). Similarly, modelling studies investigating the impact of observed stratospheric ozone depletion and temperature change over the past decade found that although the resulting increase in OH is compatible with the observed decrease in trend, by themselves they are insufficient to account for the entire decrease in growth rate (Bekki and Law, 1997;Fuglestvedt et al, 1994).…”
Section: Decadal Changes In Methane Growth Ratesmentioning
confidence: 73%
See 2 more Smart Citations
“…For most substances this information is insufficient enough to estimate this lifetime, with methyl chloroform (1,1,1-trichloroethane, CHaCC13) being the exception. That is, ground-level atmospheric concentrations of ca3cel 3 have been continuously measured worldwide since 1978 in Atmospheric Lifetime Experiment/Global Atmospheric Gases Experiment/Advanced Global Atmospheric Gases Experiment (ALE/GAGE/AGAGE) [Prinn et al, 1983b[Prinn et al, , 1992[Prinn et al, , 1995. AIF./GAGE/AGAGE is a major ground-based in situ network providing measurements of long-lived gases such as chlorofluorocarbons [Worm Meteorological Organization (WMO), 1998].…”
Section: Introductionmentioning
confidence: 99%